2022
DOI: 10.14309/ctg.0000000000000518
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Colorectal Adenomas and Cancer Using Volatile Organic Compounds in Exhaled Breath: A Proof-of-Principle Study to Improve Screening

Abstract: INTRODUCTION: Early detection of colorectal cancer (CRC) by screening programs is crucial because survival rates worsen at advanced stages. However, the currently used screening method, the fecal immunochemical test (FIT), suffers from a high number of false-positives and is insensitive for detecting advanced adenomas (AAs), resulting in false-negatives for these premalignant lesions. Therefore, more accurate, noninvasive screening tools are needed. In this study, the utility of analyzing volatile … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…The majority (n = 68) analyzed CRC cases compared to controls and eight studies included adenomas [ 33 , 36 , 45 , 68 , 69 , 96 , 97 , 98 ]. VOCs were analyzed in several biological matrices, including feces (n = 11) [ 31 , 33 , 36 , 49 , 52 , 63 , 87 , 89 , 90 , 92 , 98 ], urine (n = 9) [ 34 , 35 , 62 , 65 , 74 , 75 , 78 , 80 , 82 ], breath (n = 10) [ 28 , 29 , 40 , 51 , 60 , 61 , 70 , 72 , 85 , 96 ], blood (n = 21) [ 37 , 38 , 43 , 44 , 45 , 46 , 48 , 53 , 56 , 57 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority (n = 68) analyzed CRC cases compared to controls and eight studies included adenomas [ 33 , 36 , 45 , 68 , 69 , 96 , 97 , 98 ]. VOCs were analyzed in several biological matrices, including feces (n = 11) [ 31 , 33 , 36 , 49 , 52 , 63 , 87 , 89 , 90 , 92 , 98 ], urine (n = 9) [ 34 , 35 , 62 , 65 , 74 , 75 , 78 , 80 , 82 ], breath (n = 10) [ 28 , 29 , 40 , 51 , 60 , 61 , 70 , 72 , 85 , 96 ], blood (n = 21) [ 37 , 38 , 43 , 44 , 45 , 46 , 48 , 53 , 56 , 57 , 66 , 67 ,…”
Section: Resultsmentioning
confidence: 99%
“…Observations of SCFAs between studies were inconsistent, but they were repeatedly reported as important VOCs [ 28 , 41 , 72 ]. Similarly, lactic acid was raised in concentration in CRC cases [ 96 ]. No compounds related to the TCA cycle were reported.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, 22 studies employed VOC analysis for the diagnosis of colorectal cancer ( 7 , 28 46 , 48 , 49 ), 9 studies utilized e-nose technology ( 25 , 26 , 50 55 , 58 ), and one study used both VOC analysis and e-nose ( 47 ). In the VOC studies, 10 studies used breath samples ( 7 , 28 30 , 38 , 39 , 41 43 , 49 ), 6 studies used urine samples ( 32 , 37 , 44 46 , 48 ), 5 studies used fecal samples ( 31 , 33 , 35 , 36 , 40 ), and one study used salivary sample ( 34 ). Most studies used MS-based techniques, principally GC-MS (n=7), TD-GC-MS (n=4), FAIM (n=4), and SIFT-MS (n=2).…”
Section: Resultsmentioning
confidence: 99%
“…Due to the lack of standardization in sample collection, handling, and storage, technical barriers exist in measuring and analyzing various VOC characteristics during sampling, whether it involves alveolar air, urine, or feces. In several studies, exhaled breath was collected into a bag and subsequently analyzed ( 28 , 29 , 33 , 38 40 , 42 , 50 ). The use of bag collection aligns more closely with real-world medical applications.…”
Section: Discussionmentioning
confidence: 99%
“…In a multicenter prospective study, breath samples from 382 FIT-positive Dutch patients were collected. A biomarker profile was established based on ten discriminatory VOCs and this profile could discriminate CRCs ( N =30) from controls ( N =84) with a sensitivity and specificity of 80 and 70%, respectively 52 . Markar et al .…”
Section: Introductionmentioning
confidence: 99%